Orientalist Gregor Schoeler and the Codification of the Qurʾan - Abdulsattar Mull, Mustafa; Abdulwahhab Hussein, Hussein (International Journal of Psychosocial Rehabilitation, 2020)
Praise should be first to Allah for giving me patience and guidance during the course of writing the present study. Before printing was widely adopted in the 19th century, the Quran was transmitted in manuscripts made by calligraphers and copyists. The earliest manuscripts were written in ijāzī-type script.